Living with complexity; marshalling resources: a systematic review and qualitative meta-synthesis of lived experience of mental and physical multimorbidity. Issue 1 (December 2015) - Coventry, Peter; Small, Nicola; Panagioti, Maria; Adeyemi, Isabel; Bee, Penny
Abstract Background Multimorbidity poses a major health burden worldwide yet most healthcare is still orientated towards the management of single diseases. Literature on the experience of living with multimorbidity is accumulating but has not yet been synthesised in a manner conducive to informing the design of self-management interventions for this population. This study aimed to systematically review and synthesise findings from published, in-depth qualitative studies about the experience of multimorbidity, with a view to identifying the components and motivation for successful self-management in this population. Methods Systematic review of and meta-synthesis of qualitative studies that evaluated patient experience of living with and/or self-managing mental and/or physical multimorbidity. MEDLINE, Embase, PsycINFO, CINAHL, and ASSIA along with reference lists of existing reviews and content pages of non-indexed specialists comorbidity journals were searched. Results Nineteen studies from 23 papers were included. A line of argument synthesis was articulated around three third-order constructs: 1) Encounters with complexity; 2) Marshalling medicines, emotions, and resources; and 3) Self-preservation and prevention. Our interpretation revealed how mental and physical multimorbidity is experienced as moments of complexity rather than mere counts of illnesses. Successful self-management of physical symptoms was contingent upon the tactical use of medicines, whilst emotional health was more commonly managed by engaging in behavioural strategies, commonly with a social or spiritual component. Motivations for self-management were underpinned by a sense of moral purpose to take responsibility for their health, but also by a desire to live a purposeful life beyond an immediate context of multimorbidity. Conclusions Understanding how people experience the complexities of mental and physical multimorbidity may be crucial to designing and delivering interventions to support successful self-management in this population. Future self-management interventions should aim to support patients to exert responsibility and autonomy for medical self-management and promote agency and self-determination to lead purposeful lives via improved access to appropriate social and psychological support.